MonTI 2020
DOI: 10.6035/monti.2020.12.07
|View full text |Cite
|
Sign up to set email alerts
|

Accessible scenic arts and Virtual Reality: A pilot study with aged people about user preferences when reading subtitles in immersive environments

Abstract: Accessible scenic arts and Virtual Reality: A pilot study with aged people about... 215 Resumen El auge de los desarrollos tecnológicos en realidad virtual y otras formas de contenido inmersivo, como el video 360º, se ha convertido en un reto para el concepto de liveness en las artes escénicas, y resulta necesaria una revisión en los estudios de traducción audiovisual. La inclusión de estudios de recepción de subtítulos en este nuevo medio basado en realidad virtual es necesario. En el campo específico de los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Likewise, the presentation of Easy-to-Read subtitles is supported. Results from conducted tests have preliminarily proven that Easy-to-Read subtitles are preferred over tradditional subtitles by elderly participants when watching VR360 clips from an opera performance [48]. That recent study has also confirmed the positive attitude of the elderly towards the consumption of VR360 content for enjoying culture and arts.…”
Section: Subtitlingmentioning
confidence: 71%
“…Likewise, the presentation of Easy-to-Read subtitles is supported. Results from conducted tests have preliminarily proven that Easy-to-Read subtitles are preferred over tradditional subtitles by elderly participants when watching VR360 clips from an opera performance [48]. That recent study has also confirmed the positive attitude of the elderly towards the consumption of VR360 content for enjoying culture and arts.…”
Section: Subtitlingmentioning
confidence: 71%
“…Given the lessons learned and still open questions, future work will be targeted at:  Exploring the adoption and benefits of hybrid and advanced presentation modes and strategies, based on the dynamic user's and speaker's positions and viewpoints, as well as on the presented VR scenes.  Exploring the adoption and benefits of Easy-to-Read subtitles [33] in 3D VR scenes and environments, due to identified difficulties in following the subtitles for specific (fast and high-motion) scenes. …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the player has been built by making use of HTML5 and JavaScript, and by adopting widespread web components and APIs, such as: dash.js 28 (the reference player for DASH), three.js, 29 WebXR, 30 and IMSC rendering libraries. 31 In addition, the player includes the necessary technological solutions to enable multi-screen scenarios in a synchronized and interactive manner, in both fully web-based and Hybrid Broadcast Broadband TV (HbbTV) [15] scenarios, as described in [24].…”
Section: Technologymentioning
confidence: 99%